Immune checkpoint inhibitors for PD-1/PD-L1 axis in combination with other immunotherapies and targeted therapies for non-small cell lung cancer - Mussafi, Ofek; Mei, Jie; Mao, Wenjun; Wan, Yuan (Frontiers in Oncology, 2022)
It has been widely acknowledged that the use of immune checkpoint inhibitors (ICI) is an effective therapeutic treatment in many late-stage cancers. However, not all patients could benefit from ICI therapy. Several biomarkers, such as high expression of PD-L1, high mutational burden, and higher number of tumor infiltration lymphocytes have shown to predict clinical benefit from immune checkpoint therapies. One approach using ICI in combination with other immunotherapies and targeted therapies is now being investigated to enhance the efficacy of ICI alone. In this review, we summarized the use of other promising immunotherapies and targeted therapies in combination with ICI in treatment of lung cancers. The results from multiple animals and clinical trials were reviewed. We also briefly discussed the possible outlooks for future treatment.